(untitled) (Education in the 21st Century, 2023)
Puppet therapy is one of the most widely used art technologies in art therapy today, which reveals the phenomenon of puppets in a new sense in art pedagogy as a new pedagogical “tool” from the aspect of role behavior development, relieving emotional tension, preventing or correcting behavioral disorders. Its different types are distinguished not only by the way they are performed, but also by the direction of the work with the child: corrective, informative, regulatory, etc. Puppet therapy is often intertwined with imagotherapy and drama therapy, where one of the most important issues in the development of a person’s personality- the study of his image, becomes a priority. Puppet therapy is intended for children of all ages, but for children of different ages, its role, significance and impact, the functions performed are different. This interesting art technology is implemented individually and in groups. Puppet therapy has a multifaceted effect on the regulation of child behavior and emotional disorders.